ПОЛІНЕОПЛАЗІЯ ВОЛОСКОВОКЛІТИННОГО ЛЕЙКОЗУ ТА ГЕПАТОЦЕЦЮЛЯРНОГО РАКУ: ВИПАДОК З ПРАКТИКИ - Starchenko, I.I.; Filenko, B.M.; Royko, N.V.; Kornilova, I.V.; Vynnyk, N.I. (PH Akademperiodyka, 2023)
Multiple primary malignant tumors are characterized by independent occurrence and development of two or more malignant neoplasms in the same patient. We present an extremely rare case of synchronous double primary malignancies, hairy cell leukemia and hepatocellular carcinoma with lethal outcome. Diagnosis of hepatocellular carcinoma was difficult due to the presence of lymphoproliferative disease, which complicated the visualization of the process using ultrasonography. Carcinomatous emboli of hepatocellular carcinoma in small pulmonary arteries without the formation of metastatic foci have led to clinical manifestations typical of pulmonary embolism, pulmonary hypertension and severe respiratory failure. In lymphoproliferative diseases it is necessary to take into account the possibility of the development of another malignant neoplasm, which can be “buried” by tumor infiltration.